2008
DOI: 10.1007/s10562-008-9498-1
|View full text |Cite
|
Sign up to set email alerts
|

New Data of Nonlinear Phenomenon in the Heterogeneous Enantioselective Hydrogenation of Activated Ketones

Abstract: Results on nonlinear phenomenon (NLP) in the liquid phase hydrogenation of methyl benzoylformate (MBF) and pyruvaldehyde dimethyl acetal (PA) on chiral Pt-cinchona catalyst are reported for the first time (enantiomeric excess 90-95%). The new data support the conclusions of the NLP studies on ethyl pyruvate (EP) and ketopantolactone (KPL). Namely, the order of the adsorption strengths of the parent cinchona alkaloids are: CD [ CN [ QN * QD and the results of the NLP measurements indirectly verify the so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The application of binary mixtures of modifiers, which afford opposite enantiodifferentiation when applied as single modifiers, led to the discovery of the nonlinear behavior and the inversion of enantioselectivity. Following these earlier investigations a series of other studies have revealed that subtle structural changes of the modifier or its concentration as well as changing the solvent , and even hydrogen pressure can result in inversion of enantioselectivity. Investigations reported until 2009 have been summarized by Bartók .…”
Section: Hydrogenation Of Co Bondsmentioning
confidence: 99%
“…The application of binary mixtures of modifiers, which afford opposite enantiodifferentiation when applied as single modifiers, led to the discovery of the nonlinear behavior and the inversion of enantioselectivity. Following these earlier investigations a series of other studies have revealed that subtle structural changes of the modifier or its concentration as well as changing the solvent , and even hydrogen pressure can result in inversion of enantioselectivity. Investigations reported until 2009 have been summarized by Bartók .…”
Section: Hydrogenation Of Co Bondsmentioning
confidence: 99%
“…It has been recognized, for instance, that the cinchona alkaloids have many internal-rotation degrees of freedom, ,,, but it is not yet clear how those become reduced upon adsorption and complexation with the reactant (if at all). , In fact, it is not even known if the modifier:reactant adduct mentioned before forms directly on the surface or previously in solution. Certainly, the nature of the solvent is critical, affecting not only enantioselectivity but also total activity; it would seem that better solvents for the modifier facilitate reversible adsorption, and with that improve catalytic performance. ,, The competitive adsorption of different modifiers defines the nature of the surface modification as well, and can even lead to enantioselectivity inversion from the preferential production of one enantiomer to the other; ,, an early example of this type of inversion, due to changes in the bulkiness of the ether function of the modifier, is illustrated in Figure . The silanol groups of silica supports may also interact with the chiral modifier, and in some cases improve enantioselectivity .…”
Section: Adsorbates As Co-catalysts or Catalyst Modifiersmentioning
confidence: 99%